'A failure of language': Achieving layers of meaning in graphic journalism. (January 2014) - Schack, Todd
The power and the promise of the genre of graphic journalism (or graphic non-fiction) resides not simply in the form's juxtaposition of text and image, but in the manners in which such juxtaposition is able to create an emotive immediacy and a visceral impact that is the aim of the best of literary journalism. Further, when certain subjects, especially those of a serious nature such as Israeli/Palestinian violence or the drug-related carnage of Juárez, Mexico, are represented via this medium (as in Joe Sacco's Palestine and Charles Bowden's Dreamland, respectively), this immediacy and impact are accomplished through certain formalistic devices that the genre is particularly suited to deliver. This article seeks to show the way in which one such example, Dreamland, is instructive in creating a powerful journalistic representation of a subject via this image/text relationship.